Kombinasi Aerobic dan Resistance Training terhadap Kontrol Glukosa Darah pada Pasien Diabetes Melitus (DM) - I Putu Adi Suryawan; Debie Dahlia; Dhika Ayu Kurnia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the effect of a combination of aerobic and resistance training on blood glucose control in DM patients. The method used is a systematic review of the Scopus, Embase, EBSCO, ScienceDirect and ProQuest databases. The results showed that aerobic training carried out 5-6 times per week (150 hours per week) by running or cycling and resistance training performed 2-3 times per week (8-10 exercises per session) using weights, resistance bands, or body weights provided a positive impact on blood glucose control. In conclusion, the combination of aerobic and resistance training performed with the recommended frequency, duration, intensity and repetition can improve glycemic control in DM patients with indicators of blood sugar stability and HbA1c. Keywords: Aerobic Training, DM, Blood Glucose, Resistance Training